2019
DOI: 10.29252/johe.8.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to fatal road traffic accidents in the South of Kerman during the period from 2013 to 2017, Iran

Abstract: Article InfoBackground: Several factors influence the growth in the number of road traffic accidents and the resulting death rate. Road accident scenarios can be considered in different seasons and time intervals. In the present study, the role of factors effective in the growth of the number of accidents was explored in the south of Kerman during the period from 2013 to 2017. Materials and Methods: In this cross-sectional study, the data were collected from the Traffic Police Unit's database in the south of K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Environmental factors are such as road geometry, terrain conditions or foggy weather which can interfere with the driver's vision, as well as slow-paced and fast-paced vehicles mixing in one traffic. The study by Nasiri et al (13) found that traffic accidents which occur on main roads have a 1.30 times greater risk of causing death than accidents that occur on village roads (OR 1.30; 95% CI 1.02-1.70; P= 0.04).…”
Section: Introductionmentioning
confidence: 97%
“…Environmental factors are such as road geometry, terrain conditions or foggy weather which can interfere with the driver's vision, as well as slow-paced and fast-paced vehicles mixing in one traffic. The study by Nasiri et al (13) found that traffic accidents which occur on main roads have a 1.30 times greater risk of causing death than accidents that occur on village roads (OR 1.30; 95% CI 1.02-1.70; P= 0.04).…”
Section: Introductionmentioning
confidence: 97%
“…Although only 20% of the world vehicles are in poor and developing countries [7], the main cause of disability and untimely deaths [8] and 85% to 90% of lost years related to road accidents are in these countries [7]. Traffic accidents are the main cause of years of life lost and the second leading cause of death in Iran as a developing country [9][10][11]. Overall, it accounts for about 2.5% of the world's traffic accidents [12].…”
Section: Introductionmentioning
confidence: 99%
“…however, excessive speed is the main cause of fatalities (OR = 5.3; p ≤ 0.05) followed by breaking other road rules, in particular overloading and dangerous parking (OR = 4, 9 vs 2.5; p ≤ 0.05). In Iran, especially in the South of Kerman city, over speed (OR = 1.90; 95% CI = 1.40 -2.50; p < 0.001) and deviation to the left lane (OR = 2.20; 95% CI = 1.70 -2.90; p-value < 0.001) were more likely to lead to death than drowsiness and inattention to the front[18].…”
mentioning
confidence: 97%